Characterization of Fringing Electric Field (FEF) as oil sensor / Rosidah Md Jalani - Md Jalani, Rosidah (2013)
A fringing electric field (FEF) sensor is one of the sensors that have been used to measure the material properties such as viscosity, moisture content, temperature, hardness and degree of cure. This project is a study about the steps on designing, fabricating and testing fringing electric field (FEF) as oil sensor. Detailed explanations on how the FEF sensitivity to the oil due to the effects of the electrode size is presented. Simulations are using Finite Element Method Magnetics (FEMM) and the FEF sensor then has been fabricated on the printed circuit board (PCB). This paper also contains the performance between three type sensors and compared based on the width of fingers. Experiment is conducted using Dual Display LCR Meter. The simulation and experimental data obtained is to characterize the FEF sensor by comparing it. The final results show that the greater width of FEF finger, the higher capacitance it will be